THE INFLUENCE OF FAMILY ENVIRONMENT AND PERCEPTION ON SCHOOL ENVIRONMENT TOWARDS ENGLISH LEARNING ACHIEVEMENT - Sumarno Sumarno; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2018)
The purposes of this research are to find out (1) The role of family and perception on school environment simultaneously towards English learning achievement of SMK Negeri students at East Jakarta. (2) The influence of family environment towards English learning achievement of SMK Negeri students at East Jakarta. (3) The influence of perception on school environment towards English learning achievement of SMK Negeri students at East Jakarta. The method that used in this research is survey with correlational technique. The population of the reaserh are all students of X level of SMK Negeri 5, 7 and 40 at East Jakarta totally 767 students. The samples are 89 students. The results of this research draw (1) there are significant simultaneously influences of family environment and perception on school environment towards English learning achievement of SMK Negeri students, East Jakarta. It is proven with sig score = 0,000 < 0,05 and Fcount = 31,406. The variables of family environment and perception on school environment simultaneously distribute 44,9 %  towards English learning achievement. (2) There is a significant influence of family environmet towards English learning achievement of SMK Negeri students, East Jakarta. It is proven with sig score sig = 0,001 < 0,05 and tcount = 3,312. (3) There is a significat influence of perception on school environment towards English learning achievement of SMK Negeri students, East Jakarta. It is proven with sig score = 0,000 < 0,05 and  tcount = 3,718. Key words : Family environment, Perception on school environment, English learning achievement